Long-term outcome and necessity of liver transplantation in infants with biliary atresia are independent of cytokine milieu in native liver and serum. (November 2018) - Madadi-Sanjani, Omid; Kuebler, Joachim F.; Dippel, Stephanie; Gigina, Anna; Falk, Christine S.; Vieten, Gertrud; Petersen, Claus; Klemann, Christian
Highlights: 22 immunomodulatory mediators detectable in liver and sera of biliary atresia infants. No correlation of inflammatory mediators and Kasai-procedure outcome. Immunomodulatory mediators are unsuitable predictors for biliary atresia course. Abstract: Purpose: Biliary atresia (BA) is a rare disease of unknown pathogenesis in infants characterized by an inflammatory, progressive destruction of the biliary system and deterioration of liver function. The standard treatment for BA is a Kasai-hepatoportoenterostomy (KPE). However, liver transplantation (LTX) becomes necessary in about 50–80% of cases. Therefore, some authors advocate for primary LTX in BA, but this would require early markers to predict which children would benefit from KPE or to show rapid progression to liver cirrhosis (RLC) instead. Methods: Snap-frozen liver biopsies and sera samples of 57 infants with BA were collected during KPE. Clinical and follow-up data were assessed via the biliary atresia and related diseases registry (BARD-online.com ). Protein-levels of 25 pro- and anti-inflammatory mediators of 49 infants were assessed via multiplex protein-immunoassay and analyzed by t -test as well as multidimensional principal component analysis. Results: 22 different immunomodulatory mediators were detectable in livers of children with BA, while serum protein levels were very low to undetectable. Following KPE, 33 BA patients showed RLC that required early LTX, while 24 had favorable course of disease with long-term survival with native liver (SNL). There were no significant differences between RLC and SNL in terms of local (from liver samples) nor systemic (from sera) immunomodulatory mediators. Protein levels were much lower in sera than in livers without statistical correlation. Conclusion: Our data suggest that local or systemic immunomodulatory mediators are unsuitable for predicting the disease course of BA. Thus, no deduction for optimal treatment strategy can be drawn. Collectively, we conclude that in BA, the degree of inflammation and protein microenvironment in the liver at the time-point of KPE are dismissible factors for the future course of disease.